Pembelajaran Tematik Pendidikan Anak Usia Dini dalam Kurikulum 2013 - Vava Imam Agus Faisal (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2015)
Studying the theme has an aim to give knowledge about the importance of thematic learning in early children education. Learning is students’ interaction process with their teacher and their source study of an environment study. Thematic learning as one of the learning models emphasizes the importance of whole student development. Thematic learning model has already become accustom done by educator, but it did not reach the optimum point yet. It is necessary to increase the teachers quality to do thematic learning that appropriate with the obtain curriculum. The emergence of curriculum 2013 is the improvement of the curriculum which emphasize to learning process. Curriculum 2013 carried the developing of constructivism curriculum. It is more flexible in implementation but it gives more spaces to the children to develop their potential. Orientation of curriculum 2013 is the increasing and balancing among attitude competence, skill, and knowledge. The process of thematic learning in early children education must be operated in a reasonable way.